1985
DOI: 10.1021/bi00331a018
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman study on binding of chloride to the chromophore of halorhodopsin

Abstract: The resonance Raman spectrum of halorhodopsin, a retinoid protein with light-dependent chloride pumping activity, was observed in the presence and absence of chloride in H20 and D20. The frequency of the in-phase C=C stretching mode was shifted from 1528 to 1530 cm-' upon removal of chloride, in accordance with what was expected from the shift of the wavelength for the absorption maximum from 576 to 567 nm. The chloride effect was also found with the C=NH stretching modes of the protonated Schiff base, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
90
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 31 publications
14
90
0
Order By: Relevance
“…In HR from H. salinarum the exclusion size of anions was determined at an ionic radius of 1.65 A Ê , i.e. sulfate does not cause color changes in HR (Maeda et al, 1985;Schobert & Lanyi, 1986). In contrast, a small but measurable blue shift is demonstrated for sulfate in D85T.…”
Section: Brmentioning
confidence: 99%
“…In HR from H. salinarum the exclusion size of anions was determined at an ionic radius of 1.65 A Ê , i.e. sulfate does not cause color changes in HR (Maeda et al, 1985;Schobert & Lanyi, 1986). In contrast, a small but measurable blue shift is demonstrated for sulfate in D85T.…”
Section: Brmentioning
confidence: 99%
“…One of the sites (Site I) is relatively non-specific for C1-and will bind many other monovalent anions ). This site is near, but not on, the retinal Schiff base chromophore (Steiner et al 1984, Maeda et al 1985. Chloride binding to this site raises the pKa of the Schiff base by about 2 units (Steiner et al 1984) and stabilizes the 580 nm intermediate in the photocycle (Steiner et al 1984, Lanyi andVodyanoy 1986).…”
Section: Ci-binding To Amino Acid Residuesmentioning
confidence: 99%
“…17−20 These have shown that Cl − ions usually bind to the vicinity of the protonated Schiff base linkage, as studied by Raman spectroscopy. 21,22 The high-resolution structure of shR reveals that the chloride anion forms part of the retinal protonated Schiff base (PSB) counterion complex and replaces Asp85 of BR. In the case of halorhodopsin from N. pharaonis, Sato et al proposed the existence of Cl − binding or interacting sites in both the extracellular and cytoplasmic channels.…”
mentioning
confidence: 99%